2019
DOI: 10.1039/c9mt00077a
|View full text |Cite
|
Sign up to set email alerts
|

The role of cysteine and sulfide in the interplay between microbial Hg(ii) uptake and sulfur metabolism

Abstract: Mercury uptake by E. coli in the presence of excess cysteine is facilitated by the biodegradation of cysteine to sulfide and the formation of mercury sulfide species. The deletion of a key cysteine desulfhydrase gene (decR) limits the uptake of mercury in the presence of excess cysteine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 64 publications
0
36
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15] This methodology has led to current Hg(II) biouptake paradigms, which include the passive uptake of neutral Hg(II)-sulfide complexes (e.g., HgS 0 or Hg(HS)2 0 ) [8][9][10][11] and the active uptake of Hg (II) complexes with LMW thiols (e.g., Hg(cysteine)2). 12,13 However, microbes can alter extracellular Hg(II) speciation by the degradation or secretion of Hg(II)-binding ligands (e.g., sulfide and cysteine) [16][17][18][19][20] as well as cell-associated Hg(II) speciation via reactions with cellular S-containing ligands. [16][17][18][21][22][23][24] Therefore, predictions for Hg(II) speciation based on the initial composition of the exposure medium are not always accurate throughout the duration of the assay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15] This methodology has led to current Hg(II) biouptake paradigms, which include the passive uptake of neutral Hg(II)-sulfide complexes (e.g., HgS 0 or Hg(HS)2 0 ) [8][9][10][11] and the active uptake of Hg (II) complexes with LMW thiols (e.g., Hg(cysteine)2). 12,13 However, microbes can alter extracellular Hg(II) speciation by the degradation or secretion of Hg(II)-binding ligands (e.g., sulfide and cysteine) [16][17][18][19][20] as well as cell-associated Hg(II) speciation via reactions with cellular S-containing ligands. [16][17][18][21][22][23][24] Therefore, predictions for Hg(II) speciation based on the initial composition of the exposure medium are not always accurate throughout the duration of the assay.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, microbes can alter extracellular Hg(II) speciation by the degradation or secretion of Hg(II)-binding ligands (e.g., sulfide and cysteine) [16][17][18][19][20] as well as cell-associated Hg(II) speciation via reactions with cellular S-containing ligands. [16][17][18][21][22][23][24] Therefore, predictions for Hg(II) speciation based on the initial composition of the exposure medium are not always accurate throughout the duration of the assay. In contrast, directly tracking the cell-associated Hg(II) coordination environment during Hg exposure assays can provide insight into the Hg(II) uptake and methylation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…They also suggested that the uptake could be mediated by thiol-containing membrane proteins and that adsorption would be a first step in the methylation process ( An et al, 2019 ). These ligand-exchange reactions at the cell surface have been considered as a key step in the uptake of Hg for both methylating ( An et al, 2019 ), and non-methylating strains ( Mishra et al, 2017 ; Thomas et al, 2018 , 2019 ). However, the role of the cell surface thiols in Hg methylation has been recently discarded by reporting that the blocking of these surface ligands did not decrease Hg methylation ( Thomas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For that, we employed High Energy Resolution Fluorescence Detected – X-ray Absorption Near Edge Structure Spectroscopy (HERFD-XANES) to speciate Hg ligands and synchrotron nano X-ray fluorescence (nano-XRF) and transmission electron microscopy combined to X-ray energy dispersive spectroscopy (TEM-X-EDS) to locate Hg. HERFD-XANES has been proved highly sensitive to probe Hg species ( Manceau et al, 2015b ; Proux et al, 2017 ; Thomas et al, 2019 , 2020 ) and we specifically questioned the forms of IHg and MeHg in the two bacteria. We hypothesized that Hg speciation, particularly coordination environment, was affected by Hg concentration and was related to the ability to methylate Hg.…”
Section: Introductionmentioning
confidence: 99%
“…The binding of MeHg to cysteine has also been demonstrated in fish muscle [28]. Furthermore, addition of thiols e.g., cysteine, has been shown to either enhance or suppress MeHg formation in bacteria culture assays depending on the added concentration [20,29].…”
Section: Introductionmentioning
confidence: 98%